PENGARUH TEOLOGI EKARISTI IGNATIUS ANTIOKHIA TERHADAP ENSIKLIK ECCLESIA DE EUCHARISTIA - Yakin Ciptamulya (P3TK, Sanata Dharma University, 2014)
In the Encyclical of Ecclesia de Eucharistia, John Paul II states that Eucharist unites Church with God. In Eucharist, the presence of Christ is real. As a consequence, understanding Eucharist as merely series of rubrics is a form of reduction of the Eucharist. In the Encyclical, the Pope recalled the thought of Ignatius of Antioch on the Eucharist. Both John Paul II and Ignatius stated that Eucharist is a thanksgiving on the salvation of God. Eucharist is an invitation of God for the Church to live in the presence of God. The living experience of loving God supports the Church in transforming the world. The Church receives the power of Loving God in the Eucharist that strengthens each witness to live an exemplary Christian life here and now.